2012
DOI: 10.1002/anie.201201042
|View full text |Cite
|
Sign up to set email alerts
|

Selective Detection of Ethylene Gas Using Carbon Nanotube‐based Devices: Utility in Determination of Fruit Ripeness

Abstract: This research was supported (in part) by the U.S. Army Research Office under contract W911NF-07-D-0004. B.E. is grateful to the German Academy of Sciences Leopoldina for a postdoctoral fellowship (LPDS 2009-8). We thank S. L. Buchwald for the usage of computational resources, J. J. Walish for fabricating the device holder, and J. G. Weis for SEM measurements.Supporting information for this article is available on the WWW under http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
207
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(213 citation statements)
references
References 24 publications
3
207
0
3
Order By: Relevance
“…The system by Agar et al [29] can be adapted to be used in GC that will be described in the following. The sensor described by Esser et al [26] showed very good performances for such a relatively simple sensor. So far, only research on this topic is presented.…”
Section: (B) Electrochemical Sensorsmentioning
confidence: 97%
See 1 more Smart Citation
“…The system by Agar et al [29] can be adapted to be used in GC that will be described in the following. The sensor described by Esser et al [26] showed very good performances for such a relatively simple sensor. So far, only research on this topic is presented.…”
Section: (B) Electrochemical Sensorsmentioning
confidence: 97%
“…A chemoresistive sensor device was described by Esser et al [26,27] in 2012. In general, a chemoresistive sensor is a device that detects a gas through a change of the resistivity of an area or surface on the sensor induced by chemical bindings of the gas molecules.…”
Section: (B) Electrochemical Sensorsmentioning
confidence: 99%
“…For this reason, CNT networks, mats, and films, which are less expensive and easier to manufacture than individual CNTs, have been employed as sensor components. [3][4][5][6] Many studies have shown that these types of CNT gas sensors can be used to detect N 2 , 7 CO 2 , 8,9 H 2 O 10,11 H 2 , 12,13 and other gases, [14][15][16][17][18][19] besides O 2 , NO 2 , and NH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] High selectivities towards single gas species have been recently reported via modifying the inorganic surface of nanostructured semiconductors with a defined organic functionality. [6][7][8][9] Theoretical simulations based on ab-initio density functional theory (DFT) for a system composed of SnO2 NWs modified with a defined self assembled monolayer (SAM) elucidated the reason for the high selectivity of such gas sensor: the energetic position of the SAM-gas frontier orbitals with respect to the NW Fermi level have been identified to be the crucial factor to ensure an efficient charge transfer upon gas-SAM binding interactions and thus to sense or discriminate a certain gas species. [7] The high flexibility of organic surface modifications in terms of functional groups as well as their sterical and electronic structure possibly might enable the targeted design of various specific gas sensors.…”
mentioning
confidence: 99%